Comparison of the accuracy of classification models to estimate healthcare use and costs associated with COPD exacerbations in Saskatchewan, Canada: A retrospective cohort study - Kuwornu John Paul; Teare Gary F.; Quail Jacqueline M.; Forget Evelyn; Muthukumarana Saman; Wang Xiaoyun E.; Osman Meric; Lix Lisa M. (Canadian Journal of Respiratory Therapy)
Objective